Women’s performance at university extension in Mato Grosso Federal University - Mattos, Sandra Jung de (2023)
During its early years, Mato Grosso Federal University used to have a key role of interaction with society through extension activities. This paper aims to analyse the participation of women in extension actions as academic formation process, knowledge production and dialog with the community. To do so, documents archived at different sectors of the university have been used. The analysis is founded on the theoretical principles of New Cultural History (Burke, 1992) and Women’s History (Perrot, 2020; Scott, 2008). The documents investigated showed that women, although in small number, performed key roles acting as coordinators of extension actions and had a meaningful impact in the university’s academic and managerial context.